Rethinking classroom participation : listening to silent voices - Schultz, Katherine (New York : Teachers College Press, 2009)
Katherine Schultz examines the complex role student silence can play in teaching and learning. Urging teachers to listen to student silence in new ways, this book offers real-life examples and proven strategies for'rethinking classroom participation' to include all students--those eager to raise their hands to speak and those who may pause or answer in different ways.--From publisher description.
Participation and silence in the classroom -- Forms and functions of silence -- Classroom silences, classroom talk -- Student silences, curricular participation -- Learning from student silence.
Includes bibliographical references (p. 149-159) and index.
Keywords: Classroom management; Self-esteem in children; Educational psychology; Silence